Fabp4-Cre-mediated Sirt6 deletion impairs adipose tissue function and metabolic homeostasis in mice. Issue 3 (June 2017) - Xiong, Xiwen; Zhang, Cuicui; Zhang, Yang; Fan, Rui; Qian, Xinlai; Dong, X Charlie
Abstract : SIRT6 is a member of sirtuin family of deacetylases involved in diverse processes including genome stability, metabolic homeostasis and anti-inflammation. However, its function in the adipose tissue is not well understood. To examine the metabolic function of SIRT6 in the adipose tissue, we generated two mouse models that are deficient in Sirt6 using the Cre-lox approach. Two commonly used Cre lines that are driven by either the mouse Fabp4 or Adipoq gene promoter were chosen for this study. The Sirt6- knockout mice generated by the Fabp4-Cre line ( Sirt6 f/f : Fabp4-Cre) had a significant increase in both body weight and fat mass and exhibited glucose intolerance and insulin resistance as compared with the control wild-type mice. At the molecular levels, the Sirt6 f/f :Fabp4-Cre-knockout mice had increased expression of inflammatory genes including F4/80, TNFα, IL-6 and MCP-1 in both white and brown adipose tissues. Moreover, the knockout mice showed decreased expression of the adiponectin gene in the white adipose tissue and UCP1 in the brown adipose tissue, respectively. In contrast, the Sirt6 knockout mice generated by the Adipoq-Cre line ( Sirt6 f/f :Adipoq-Cre) only had modest insulin resistance. In conclusion, our data suggest that the function of SIRT6 in the Fabp4-Cre-expressing cells in addition to mature adipocytes plays a critical role in body weight maintenance and metabolic homeostasis.